2017
DOI: 10.1001/jamasurg.2017.2635
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Risk of Postsurgical General and Geriatric Complications Using the VESPA Preoperative Tool

Abstract: Preoperative assessment of older geriatric patients is feasible in the general preoperative clinic and can help identify patients at higher risk of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Screening could be achieved using a test such as the Mini-Cog[56, 57] which requires only 3-minutes for administration and thus would not add excessive burden to the preoperative assessment. The Vulnerable Elders Surgical Pathways and Outcomes Assessment (VESPA) trial includes the Mini-Cog in its preoperative risk assessment tool, and has demonstrated the feasibility of this approach[58]. Second, given the substantial impact of delirium on adverse clinical outcomes, these results suggest the need to redouble efforts for prevention of delirium, and screening for MCI could be beneficial to target high-risk patients for these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Screening could be achieved using a test such as the Mini-Cog[56, 57] which requires only 3-minutes for administration and thus would not add excessive burden to the preoperative assessment. The Vulnerable Elders Surgical Pathways and Outcomes Assessment (VESPA) trial includes the Mini-Cog in its preoperative risk assessment tool, and has demonstrated the feasibility of this approach[58]. Second, given the substantial impact of delirium on adverse clinical outcomes, these results suggest the need to redouble efforts for prevention of delirium, and screening for MCI could be beneficial to target high-risk patients for these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' physical function has also been associated with surgical outcomes for some conditions. Frailty has been associated with longer hospital lengths of stay, 3 elevated risk of postoperative complications, 4 postoperative delirium 5 and postoperative costs. 6 A review of colorectal surgeries found frailty associated with higher risk of poorer postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that there is a low likelihood of malignancy of thyroid nodules in old aged patients, these cancers have a more aggressive phenotype (27) with any postsurgical complications, rather, the functional status determined by the Lawton and Katz scales and the self-assessed inability to manage alone after discharge were the leading risk factors for surgical outcomes. They also proved that postoperative sarcopenia is a relatively frequent occurrence (30).…”
Section: Discussionmentioning
confidence: 93%